View to the health tourism between historiography and sociosemiotics - Bertoša, Mislava (Array, 2011)
The paper aims to analyse the tourist promotion of seaside and balneary destinations of the former Austro-Hungarian Monarchy, in regions which today belong to two countries: Portorož/Portorose in Slovenia, Opatija/Abbazia and Lošinj/Lussin in Croatia. Our approach combines the sociosemiotic perspective and historical research on health tourism. The sociosemiotic perspective (Landowski 1999 ; 2003) observes interactions actualized within a discourse, between individual or collective subjects who are inscribed and recognized in it. In this perspective discourse can be seen as a space of interactions where different communication strategies are distributed. These strategies determine the types of possible discursive roles for each of the two protagonists – the sender and the receiver – of the discourse that is being uttered. The coastal balneary, health and beach resorts at the Austrian Littoral developed under the influence of medical discourse that promoted the positive influence of sea, sun and mild climate for treating and recovering from many diseases (tuberculosis, scrofulous, children diseases). An important, often crucial actor in the development of a seaside balneary and health resort was medicine. Some resorts were proclaimed as winter resorts because of the mild climate in winter, some began their tourist “career” as summer seaside resorts, promoting sea bathing, exposure to sea climate, medical treatments with sea mud and brine. Others, on the other hand, had two seasons, the summer and the winter one. The health and balneary seaside resorts, such as Portorož and Lošinj became important tourist destinations in the Monarchy. The aim of the analysis is to research the way in which semiotic material from a particular cultural and historical reality has been re-elaborated: this material consists of imaginary, symbolic forms, linguistic registers, and narrative, visual and uttered configurations.